Maternal vitamin B12 deficiency detected by newborn screening: evaluation of causes and characteristics - Reischl-Hajiabadi, Anna Theresa; Garbade, Sven; Feyh, Patrik; Weiss, Karl Heinz; Mütze, Ulrike; Kölker, Stefan; Hoffmann, Georg F.; Gramer, Gwendolyn (Nutrients, 2022)
Vitamin B12 deficiency, mostly of maternal origin in newborns, is a well-treatable condition but can cause severe neurologic sequelae in infants. Early detection of vitamin B12 deficiency allows the pre-symptomatic treatment of affected children. This evaluation assesses the characteristics of maternal vitamin B12 deficiency detected by newborn screening. In a prospective single-center study, a systematic screening strategy for vitamin B12 deficiency using a combination of two second-tier strategies was applied. In addition to confirmatory diagnostics in children, the systematic work-up of vitamin B12 status was also performed for their mothers.
Im Titel erscheint die Ziffer 12 tiefgestellt
Gesehen am 29.11.2022